Old Testament criticism in the nineteenth century England and Germany - Rogerson, John W. (London, UK SPCK, 1984)
Includes bibliographical references and indexes
Keywords: Bible. O.T. -- criticism, interpretation, etc -- 19th century -- England; Bible. O.T. -- criticism, interpretation, etc -- 19th century -- Germany